2012
DOI: 10.1094/pdis-01-12-0026-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Botryosphaeria obtusa as Causal Agent of Olive Tree Branch Dieback in Tunisia

Abstract: A branch dieback of olive trees (Olea europaea L. cv. Manzanilla de Sevilla) was observed in 2010 in an orchard (50 ha), located in the Testour region of northern Tunisia. More than 50% of trees were severely damaged by the disease. Symptomatic trees presented dead branches and wilted leaves, which remained attached to the shoots, and the affected tissues appeared abnormally dark compared with the inner bark of healthy branches. Numerous pycnidia were observed on the surface of the infected branches. For diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…As regards Botryosphaeriaceae species from the genera Botryosphaeria, Diplodia, Neofusicoccum , they can cause Bot canker on grapevines [42] but also on many plants like olive trees [43] , peach trees [44] , [45] , almond trees [46] , oak [47] . Here, Botryosphaeriaceae species were very frequently isolated from grapevines, being present in 83% and 93% of the esca-foliar asymptomatic and symptomatic plants respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As regards Botryosphaeriaceae species from the genera Botryosphaeria, Diplodia, Neofusicoccum , they can cause Bot canker on grapevines [42] but also on many plants like olive trees [43] , peach trees [44] , [45] , almond trees [46] , oak [47] . Here, Botryosphaeriaceae species were very frequently isolated from grapevines, being present in 83% and 93% of the esca-foliar asymptomatic and symptomatic plants respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Since the last few years, due to the climate change and the introduction of new cultivars and cultural practices, symptoms of new diseases caused by foliar pathogens not seen before have been reported in the country (Chattaoui et al . , ). This represents an alarming situation in the olive industry, as a lot of fungal pathogens affecting leaves and fruit cause economically important olive diseases (Trapero and Blanco ).…”
Section: Introductionmentioning
confidence: 99%
“…Zebib (2011) also reported this species in Lebanese vineyards. Diplodia seriata also occurs on olive drupes in Spain (Moral et al, 2008), Tunisia (Chattaoui et al, 2012), and Croatia (Kaliterna et al, 2012). A recent study reported leaf dieback on Osmanthus sp.…”
Section: Discussionmentioning
confidence: 99%